Correctional Institution Officers' Stigma Towards Inmates with Mental Health Problems - Riyanti, Gisti Respati; Hadi, Ella Nurlaella (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Despite inmates are one group that susceptible to have mental health problem, they may also experience double stigma from people surroundings because of those condition, including from their correctional institution officer. Aims: This study aims to know correctional institution officers' stigma towards inmates with mental health problem. Methods: This is quantitative research with cross-sectional design. This research used secondary data from study about Correctional Institution Officers' Perception towards Mental Health which conducted in June 2023 towards 1654 officers in Central Java. Data was collected by self-reported using questionnaire. The selected questions consist of independent variables including demographic factors, history of seminar/training about mental health, and previous contact with someone who has mental health problem, and also the dependent variable which was level of stigma measured with EMIC-CSS instruments. Data was analyzed with chi-square test. Results: About 1161 respondents meet inclusion criteria, with 62% correctional institution officer had high stigma towards inmates with mental health problem. Age (p=0,05), length of work in correctional institution (p=0,02), and previous contact with someone who has mental health problems (p=0,04) correlate with officers' stigma towards inmates with mental health problem. Conclusion: High level of officers' stigma towards inmates with mental health problem may hinder management of mental health problem in correctional institution environment. Literacy enhancement and contact equality are needed to increase mental health awareness and decrease stigma among correctional institution officers.